نحو مشروع استثمار أموال الوقف في بوركينا فاسو في ضوء التجارب المعاصرة : دراسة فقهية تحليلية - عمر، كارمبيرى شيخ (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This research aims to develop a project that is capable of investing waqf funds in Burkina Faso. Since the government in Burkina Faso is secular, there is no Ministry of Islamic Endowments (awqaf). It is worthy of mention, though, that the concept of waqf and its investment is unclear and blurred to many Muslims. Thus, most endowments in Burkina Faso are not invested, and rather they rely on private support from the endower or the bodies that establish them, such as benevolent institution, charity organization or volunteers. This research attempts to present a solution to this problem by proposing the idea of establishing a project to invest waqf funds in Burkina Faso. It uses an inductive approach to collect and deduce the experiences of endowments in the Islamic world based on the identification of institutions and public secretariats to invest the endowments in the Islamic countries. It uses an analytical approach to analyze the legal texts, the findings and the data obtained through the practical experiences of investing waqf funds in the Islamic world, and to examine the related process in Burkina Faso. The researcher wanted to conduct a field study through personal interviews or sending questionnaires to the owners of endowments in Burkina Faso to know the status of their endowments. He also intended that the answers to the questions will be in multiple subjects without assigning a separate chapter for them. The questionnaires have been prepared as they are attached to the end of the research, but with great sadness the researcher would like to inform that because of the pandemic of Corona virus he did not receive the answers to them from the owners of the endowments. One of the most important findings of this research is to establish external sources in order to finance endowment investments in Burkina Faso in accordance with the provisions of Shari'ah Law; to revive and substitute estate endowments that have turned into wasteland in Burkina Faso; and finally, to discover new ways to invest endowments in Burkina Faso as a substitute and replacement to traditional and ineffective current practices